Wear-resistant weather-resistant super-amphiphobic coating, coating as well as preparation method and application of coating
By fluorinating and grafting reaction of nanoparticles, combined with epoxy resin and curing agent, an anti-wear and weather-resistant ultra-double coating was prepared, which solved the problem that existing materials were difficult to take into account both wear and weather resistance, and achieved double-double properties of water and glycerol and good wear and weather resistance.
Patent Information
- Application Number
- CN202411940453.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing ultra-double-spark materials are difficult to take into account both wear resistance and weather resistance, which limits their application in harsh environments.
The nanoparticles were fluorinated and modified by long-chain perfluorosilane, and the nanoparticles were further modified by ammonia siloxane grafting reaction, combined with epoxy resin and curing agent to prepare an anti-wear and weather-resistant ultra-double-spark coating.
It realizes the double-splitting function of water and glycerol, and has certain wear resistance and weather resistance, and can maintain good stability during multiple wear and long-term soaking.
Smart Images

Figure CN119684872A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of functional coating materials, and in particular relates to a wear-resistant and weather-resistant super-amphiphobic coating, a coating, and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] With the acceleration of industrialization and the increasing severity of environmental pollution, higher requirements are placed on the wear resistance and weather resistance of materials. Especially in outdoor applications, the surface of the material is susceptible to factors such as wind and rain, ultraviolet radiation and chemical corrosion, resulting in performance degradation and shortened service life. Super-amphiphobic materials, that is, materials with both super-hydrophobic and super-oleophobic properties, show great potential in the fields of self-cleaning, anti-fouling, and anti-corrosion due to their unique surface properties. However, existing super-amphiphobic materials often find it difficult to balance wear resistance and weather resistance, which limits their application in harsh environments. Therefore, it is urgent to develop a new type of wear-resistant and weather-resistant super-amphiphobic material coating in order to achieve breakthrough applications in many fields such as construction, transportation, and marine engineering. Summary of the invention
[0004] In order to address the deficiencies in the prior art, the object of the present invention is to provide a wear-resistant and weather-resistant super-amphiphobic coating, a coating and a preparation method and application thereof. The wear-resistant and weather-resistant super-amphiphobic coating provided by the present invention can realize the amphiphobic function of water and glycerol, and has certain wear resistance and weather resistance, thereby achieving long-term stability and high-efficiency protective performance of the coating.
[0005] In order to achieve the above object, the technical solution of the present invention is:
[0006] In a first aspect, the present invention provides an anti-wear and weather-resistant super-amphiphobic coating, comprising: modified nanoparticles, epoxy resin, and a curing agent, wherein the modified nanoparticles are obtained by fluorinating the nanoparticles using long-chain perfluorosilane and then grafting them using aminosiloxane; wherein:
[0007] The mass ratio of epoxy resin, curing agent and modified nanoparticles is (1-2):(1-2):5;
[0008] The mass ratio of long-chain perfluorosilane, nanoparticles and aminosiloxane is (1-3):1:(0.5-1).
[0009] Preferably, the mass ratio of epoxy resin, curing agent and modified nanoparticles is (1-1.5):(1-1.5):5;
[0010] The mass ratio of long-chain perfluorosilane, nanoparticles and aminosiloxane is (2-3):1:(0.75-1).
[0011] In one or more embodiments, the nanoparticles are selected from one or more of aluminum oxide, aluminum hydroxide, silicon dioxide and diatomaceous earth, preferably aluminum oxide.
[0012] Preferably, the particle size of the nanoparticles is 5-30 nm.
[0013] In one or more embodiments, the long-chain perfluorosilane is selected from one or more of 1H,1H,2H,2H-perfluorodecyltriethoxysilane, tridecafluorooctyltrimethoxysilane, 1H,1H,2H,2H-perfluorododecyltriethoxysilane, heptadecafluorodecyltrimethoxysilane and 1H,1H,2H,2H-perfluorododecyltrichlorosilane.
[0014] The reason for using long-chain perfluorosilane instead of short-chain perfluorosilane is that the long fluorocarbon chain carries more low-surface-energy fluorine atoms, and the resulting coating surface has a lower surface energy.
[0015] In one or more embodiments, the aminosiloxane is selected from one or more of 3-aminopropyltrimethoxysilane, 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane, N-[3-(trimethoxysilyl)propyl]ethylenediamine and 1-(3-trimethoxysilyl)propylurea.
[0016] The reason for using amino-containing siloxane instead of siloxane is that short-chain aminosiloxane overcomes steric hindrance and further compensates for the surface defects of the nanoparticles. At the same time, the amino group carried at the tail end undergoes a grafting reaction with the resin, thereby better anchoring the nanoparticles on the coating surface. Siloxane alone does not have this function.
[0017] In one or more embodiments, the epoxy resin is a bisphenol epoxy resin, and the bisphenol epoxy resin is a bisphenol A epoxy resin.
[0018] In one or more embodiments, the curing agent is an amine curing agent, and the amine curing agent is selected from one or more of ethylenediamine, diethylenetriamine and triethylenetetramine.
[0019] In a second aspect, the present invention provides a method for preparing the above-mentioned wear-resistant and weather-resistant super-amphiphobic coating, comprising the following steps:
[0020] The nanoparticles are added to an alkaline alcohol solution for activation, and then long-chain perfluorosilane is added for fluorination modification, and then aminosiloxane is added for grafting reaction to obtain modified nanoparticles;
[0021] The modified particles are mixed and emulsified with an alcohol-diluted epoxy resin and a curing agent to obtain a super-amphiphobic coating.
[0022] In one or more embodiments, in the alkaline alcohol solution, the base is aqueous ammonia, and the alcohol is ethanol, and the volume ratio of the base to the alcohol is (1-3):50.
[0023] In one or more embodiments, the fluorination modification is carried out by stirring the reaction at 40-50° C. and 300-500 rpm for 3-6 hours.
[0024] In one or more embodiments, the grafting reaction is carried out at 40-50° C. with sealed stirring at 300-500 rpm for 8-12 hours.
[0025] In one or more embodiments, after the grafting reaction, the reactants are washed with alcohol and centrifuged to obtain sinking modified particles with a solid content of 30-40%, and alcohol is added to the sinking modified particles for physical dispersion to obtain 10-15wt% modified nanoparticles.
[0026] Preferably, the alcohol is ethanol.
[0027] Preferably, the centrifugation condition is 5000-9000 r / min for 5-20 minutes.
[0028] Preferably, the physical dispersion is performed by ultrasonic dispersion, the ultrasonic frequency is 200-400W, and the ultrasonic time is 5-20min.
[0029] In one or more embodiments, in the alcohol-diluted epoxy resin and curing agent, the mass fraction of the epoxy resin is 10-15 wt %. Preferably, the alcohol is ethanol.
[0030] In one or more embodiments, the mixing and emulsification is emulsification dispersion under high shear of 10000-15000 r / min for 5-20 minutes.
[0031] The purpose of high shear emulsification is to achieve adequate dispersion.
[0032] In a third aspect, the present invention provides a method for preparing an anti-wear and weather-resistant super-amphiphobic coating using the above-mentioned anti-wear and weather-resistant super-amphiphobic coating, comprising the following steps:
[0033] The substrate is surface treated, and then the wear-resistant and weather-resistant super-amphiphobic coating is sprayed on the surface of the substrate, firstly cured at a low temperature of 50-80° C. for 1-5 hours, and then cured at a high temperature of 100-130° C. for 1-5 hours.
[0034] In one or more embodiments, the surface treatment of the substrate is to clean the substrate alternately with ethanol and water.
[0035] In one or more embodiments, the spraying is performed under a gas pressure of 0.2-6 MPa.
[0036] In one or more embodiments, when sprayed on the surface of the substrate, the amount is 0.7-1.2 g / m 2 .
[0037] In one or more embodiments, the substrate includes soft and hard substrates, such as cotton fabric, sponge, metal, wood, paper, fiber, glass, plastic, etc., which can be coated.
[0038] In a fourth aspect, a wear-resistant and weather-resistant super-amphiphobic coating is obtained by the above-mentioned preparation method.
[0039] The wear-resistant and weather-resistant super-amphiphobic coating has super-amphiphobic performance (contact angle greater than 150°) in water and glycerol, and after multiple wears, it still has super-amphiphobic performance (contact angle greater than 150°); it can still maintain good stability (contact angle greater than 150°) in long-term immersion in ethylene glycol. Therefore, the wear-resistant and weather-resistant super-amphiphobic coating prepared by the present invention has wear resistance and weather resistance.
[0040] Specifically, the wear-resistant and weather-resistant super-amphiphobic coating has a static contact angle of 153°-165° to water, preferably 153°-162°, and a static contact angle of 151°-160° to glycerol, preferably 151°-156°. After 30 wears, the wear-resistant and weather-resistant super-amphiphobic coating has a static contact angle of 160°-161° to water, and a static contact angle of 150° to glycerol.
[0041] After being immersed in ethylene glycol for 24 hours, the static contact angle of the wear-resistant and weather-resistant super amphiphobic coating is 154°-155°.
[0042] A fifth aspect is an application of the above-mentioned wear-resistant and weather-resistant super-amphiphobic coating or the above-mentioned wear-resistant and weather-resistant super-amphiphobic coating in the fields of construction, transportation or marine engineering.
[0043] One or some of the above technical solutions have the following advantages or beneficial effects:
[0044] (1) The present invention provides a wear-resistant and weather-resistant super-amphiphobic coating for preparing a wear-resistant and weather-resistant super-amphiphobic coating, wherein a long-chain perfluorosilane is used to initially modify the surface energy of nanoparticles to a low level, and then a short-chain aminosilane is used to overcome the steric hindrance and further graft the nanoparticles to eliminate local defects; at the same time, the introduction of amino groups into the nanoparticles makes it easier for the nanoparticles to chemically bond with epoxy resin, and also consumes excess hydroxyl groups; further, a small amount of epoxy resin is used to shear and emulsify the modified nanoparticles to obtain a highly stable super-amphiphobic coating, and finally a wear-resistant and weather-resistant super-amphiphobic coating is prepared, which can realize the amphiphobic function of water and glycerol and has certain wear resistance and weather resistance.
[0045] (2) The wear-resistant and weather-resistant super-amphiphobic coating prepared by the present invention can realize the amphiphobic function of water and glycerol, and the wear-resistant and weather-resistant super-amphiphobic coating can still maintain good stability in long-term immersion in ethylene glycol, and after being worn 30 times, it still has good amphiphobic function. Therefore, the wear-resistant and weather-resistant super-amphiphobic coating has certain wear resistance and weather resistance.
[0046] (3) The anti-wear and weather-resistant super-amphiphobic material coating provided by the present invention has a simple process, and a variety of combined materials with similar properties can be selected to prepare the coating, and it is suitable for curing and molding on the surface of various substrates. It provides a new idea for preparing anti-wear and weather-resistant super-amphiphobic material coating materials, and has important guiding significance for the preparation of high-performance anti-wear and weather-resistant super-amphiphobic material coatings. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0048] Figure 1 A schematic diagram of the process flow of preparing the wear-resistant and weather-resistant super-amphiphobic coating in an embodiment of the present invention is shown;
[0049] Figure 2 This is the SEM of the surface of the wear-resistant and weather-resistant super-amphiphobic coating prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0050] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0051] All drugs are commercially available.
[0052] Example 1
[0053] Reference Figure 1 The specific steps for preparing the wear-resistant and weather-resistant super-amphiphobic material coating are as follows:
[0054] (1) Add 2 g of aluminum oxide and 5 mL of ammonia water to 100 mL of ethanol and mix well. Then add 2 mL of perfluorodecyltriethoxysilane and stir in a sealed container at 300-500 rpm for 5 h at 45°C to carry out fluorination modification. Then add 1.5 mL of 3-aminopropyltrimethoxysilane and continue the grafting reaction for 10 h.
[0055] (2) After the reaction is complete, the modified particles are washed with ethanol and centrifuged at 8000 r / min for 10 minutes three times to obtain 30-40% solid content precipitated modified particles. Ethanol is added again and dispersed by 300W ultrasound for 10 minutes to obtain 10wt% modified nanoparticles.
[0056] (3) Take 50 g of the modified nanoparticles containing 10 wt% in step (2) as a sample, add 10 g of epoxy resin diluted to 10 wt% by ethanol and 1 g of amine curing agent, use an emulsifier to shear emulsify and disperse at 12000 r / min for 10 minutes to obtain a super-amphiphobic coating.
[0057] (4) Clean the substrate alternately with ethanol and water, and spray the coating evenly on the surface of the substrate with a spray gun (nozzle diameter: 1 mm) at a pressure of 0.5 MPa, with a quantitative of 1 g / ㎡. First cure at 60°C for 3 hours, then cure at 120°C for 3 hours.
[0058] Example 2
[0059] Reference Figure 1 The specific steps for preparing the wear-resistant and weather-resistant super-amphiphobic material coating are as follows:
[0060] (1) Add 2 g of aluminum oxide and 5 mL of ammonia water to 100 mL of ethanol and mix well. Then add 2 mL of perfluorodecyltriethoxysilane and stir in a sealed container at 300-500 rpm for 5 h at 45°C to carry out fluorination modification. Then add 2 mL of 3-aminopropyltrimethoxysilane and continue the grafting reaction for 10 h.
[0061] (2) Same as in Example 1, specifically:
[0062] After the reaction is complete, the modified particles are washed with ethanol and centrifuged at 8000 r / min for 10 minutes for 3 times to obtain 30-40% solid content precipitated modified particles. Ethanol is added again and dispersed at 300W ultrasonic for 10 minutes to obtain 10wt% modified nanoparticles.
[0063] (3) Take 50 g of the sample and add 15 g of epoxy resin diluted to 10 wt% by ethanol and 1.5 g of amine curing agent, and use an emulsifier at 12000 r / min for shear emulsification and dispersion for 10 minutes to obtain a super-amphiphobic coating.
[0064] (4) Clean the substrate alternately with ethanol and water, and spray the coating evenly on the surface of the substrate with a spray gun (nozzle diameter: 1 mm) at a pressure of 0.5 MPa, with a quantitative of 1.2 g / ㎡. First cure at 60°C for 3 hours, then cure at 120°C for 3 hours.
[0065] Example 3
[0066] Reference Figure 1 The specific steps for preparing the wear-resistant and weather-resistant super-amphiphobic material coating are as follows:
[0067] (1) Add 2 g of aluminum oxide and 5 mL of ammonia water to 100 mL of ethanol and mix well. Then add 3 mL of perfluorodecyltriethoxysilane and stir in a sealed container at 300-500 rpm for 5 h at 45°C to perform fluorination modification. Then add 1.5 mL of 3-aminopropyltrimethoxysilane and continue the grafting reaction for 10 h.
[0068] (2) Same as in Example 1, specifically:
[0069] After the reaction is complete, the modified particles are washed with ethanol and centrifuged at 8000 r / min for 10 minutes for 3 times to obtain 30-40% solid content precipitated modified particles. Ethanol is added again and dispersed at 300W ultrasonic for 10 minutes to obtain 10wt% modified nanoparticles.
[0070] (3) Take 50 g of the sample and add 10 g of epoxy resin diluted to 10 wt% by ethanol and 1 g of amine curing agent, and use an emulsifier at 12000 r / min for shear emulsification and dispersion for 10 minutes to obtain a super-amphiphobic coating.
[0071] (4) Same as in Example 1, specifically:
[0072] Clean the substrate alternately with ethanol and water, and spray the coating evenly on the surface of the substrate with a spray gun (nozzle diameter: 1mm) at 0.5MPa pressure, with a quantitative of 1g / ㎡. First cure at 60℃ for 3h, then cure at 120℃ for 3h.
[0073] Example 4
[0074] Reference Figure 1 The specific steps for preparing the wear-resistant and weather-resistant super-amphiphobic material coating are as follows:
[0075] (1) Add 2 g of aluminum oxide and 5 mL of ammonia water to 100 mL of ethanol and mix well. Then add 3 mL of perfluorodecyltriethoxysilane and stir in a sealed container at 300-500 rpm for 5 h at 45°C to carry out fluorination modification. Then add 2 mL of 3-aminopropyltrimethoxysilane and continue the grafting reaction for 10 h.
[0076] (2) Same as in Example 1, specifically:
[0077] After the reaction is complete, the modified particles are washed with ethanol and centrifuged at 8000 r / min for 10 minutes for 3 times to obtain 30-40% solid content precipitated modified particles. Ethanol is added again and dispersed at 300W ultrasonic for 10 minutes to obtain 10wt% modified nanoparticles.
[0078] (3) Take 50 g of the sample and add 15 g of epoxy resin diluted to 10 wt% by ethanol and 1.5 g of amine curing agent, and use an emulsifier at 12000 r / min for shear emulsification and dispersion for 10 minutes to obtain a super-amphiphobic coating.
[0079] (4) Same as in Example 1, specifically:
[0080] Clean the substrate alternately with ethanol and water, and spray the coating evenly on the surface of the substrate with a spray gun (nozzle diameter: 1mm) at 0.5MPa pressure, with a quantitative of 1g / ㎡. First cure at 60℃ for 3h, then cure at 120℃ for 3h.
[0081] Example 5
[0082] Reference Figure 1 The specific steps for preparing the wear-resistant and weather-resistant super-amphiphobic material coating are as follows:
[0083] (1) Add 2 g of aluminum oxide and 5 mL of ammonia water to 100 mL of ethanol and mix well. Then add 4 mL of perfluorodecyltriethoxysilane and stir in a sealed container at 300-500 rpm for 5 h at 45°C to carry out fluorination modification. Then add 1.5 mL of 3-aminopropyltrimethoxysilane and continue the grafting reaction for 10 h.
[0084] (2) Same as in Example 1, specifically:
[0085] After the reaction is complete, the modified particles are washed with ethanol and centrifuged at 8000 r / min for 10 minutes for 3 times to obtain 30-40% solid content precipitated modified particles. Ethanol is added again and dispersed at 300W ultrasonic for 10 minutes to obtain 10wt% modified nanoparticles.
[0086] (3) Take 50 g of the sample and add 20 g of epoxy resin diluted to 10 wt% by ethanol and 2 g of amine curing agent, use an emulsifier at 12000 r / min for shear emulsification and dispersion for 10 minutes to obtain a super-amphiphobic coating.
[0087] (4) Same as in Example 2, specifically:
[0088] Clean the substrate alternately with ethanol and water, and spray the coating evenly on the surface of the substrate with a spray gun (nozzle diameter: 1mm) at 0.5MPa pressure, with a quantitative of 1.2g / ㎡. First cure at 60℃ for 3h, then cure at 120℃ for 3h.
[0089] Comparative Example 1
[0090] Reference Figure 1 The specific steps for preparing the wear-resistant and weather-resistant super-amphiphobic material coating are as follows:
[0091] (1) Add 2 g of aluminum oxide and 5 mL of ammonia water to 100 mL of ethanol and mix well. Then add 4 mL of perfluorodecyltriethoxysilane and stir in a sealed state at 300-500 rpm for 5 h at 45°C to carry out fluorination modification. Then add 2 mL of 3-aminopropyltrimethoxysilane and continue the grafting reaction for 10 h.
[0092] (2) Same as in Example 1, specifically:
[0093] After the reaction is complete, the modified particles are washed with ethanol and centrifuged at 8000 r / min for 10 minutes for 3 times to obtain 30-40% solid content precipitated modified particles. Ethanol is added again and dispersed at 300W ultrasonic for 10 minutes to obtain 10wt% modified nanoparticles.
[0094] (3) Take 50 g of the sample and add 30 g of epoxy resin diluted to 10 wt% by ethanol and 3 g of amine curing agent, use an emulsifier at 12000 r / min for shear emulsification and dispersion for 10 minutes to obtain a super-amphiphobic coating.
[0095] (4) Same as in Example 2, specifically:
[0096] Clean the substrate alternately with ethanol and water, and spray the coating evenly on the surface of the substrate with a spray gun (nozzle diameter: 1mm) at 0.5MPa pressure, with a quantitative of 1.2g / ㎡. First cure at 60℃ for 3h, then cure at 120℃ for 3h.
[0097] Comparative Example 2
[0098] Reference Figure 1 The specific steps for preparing the wear-resistant and weather-resistant super-amphiphobic material coating are as follows:
[0099] (1) Add 2 g of aluminum oxide and 5 mL of ammonia water to 100 mL of ethanol and mix well, then add 3 mL of perfluorodecyltriethoxysilane, and stir in a sealed manner at 45° C. at a speed of 300-500 rpm for 5 h to carry out fluorination modification.
[0100] (2) Same as Example 1, specifically: after the reaction is complete, the modified particles are washed with ethanol and centrifuged at 8000 r / min for 10 minutes 3 times to obtain 30-40% solid content precipitated modified particles. Ethanol is added again and dispersed at 300W ultrasonic for 10 minutes to obtain 10wt% modified nanoparticles.
[0101] (3) The same as Example 1, specifically: take 50g of sample and add 10g of epoxy resin diluted to 10wt% by ethanol and 1g of amine curing agent, use an emulsifier at 12000r / min for shear emulsification and dispersion for 10 minutes to obtain a super amphiphobic coating.
[0102] (4) Same as Example 1, specifically: the substrate is cleaned alternately with ethanol and water, and the coating is evenly sprayed on the surface of the substrate with a spray gun (nozzle diameter: 1 mm) at a pressure of 0.5 MPa, with a quantitative of 1 g / ㎡. First, it is cured at a low temperature of 60°C for 3 hours, and then at a high temperature of 120°C for 3 hours.
[0103] Comparative Example 3
[0104] Reference Figure 1 The specific steps for preparing the wear-resistant and weather-resistant super-amphiphobic material coating are as follows:
[0105] (1) Add 2 g of aluminum oxide and 5 mL of ammonia water to 100 mL of ethanol and mix well, then add 3 mL of perfluorodecyltriethoxysilane, and stir in a sealed manner at 45° C. at a speed of 300-500 rpm for 5 h to carry out fluorination modification.
[0106] (2) Same as Example 1, specifically: after the reaction is complete, the modified particles are washed with ethanol and centrifuged at 8000 r / min for 10 minutes 3 times to obtain 30-40% solid content precipitated modified particles. Ethanol is added again and dispersed at 300W ultrasonic for 10 minutes to obtain 10wt% modified nanoparticles.
[0107] (3) The same as Example 4, specifically: take 50g of the sample and add 15g of epoxy resin diluted to 10wt% by ethanol and 1.5g of amine curing agent, use an emulsifier at 12000r / min for shear emulsification and dispersion for 10 minutes to obtain a super amphiphobic coating.
[0108] (4) Same as Example 1, specifically: the substrate is cleaned alternately with ethanol and water, and the coating is evenly sprayed on the surface of the substrate with a spray gun (nozzle diameter: 1 mm) at a pressure of 0.5 MPa, with a quantitative of 1 g / ㎡. First, it is cured at a low temperature of 60°C for 3 hours, and then at a high temperature of 120°C for 3 hours.
[0109] Comparative Example 4
[0110] Reference Figure 1 The specific steps for preparing the wear-resistant and weather-resistant super-amphiphobic material coating are as follows:
[0111] (1) Add 2 g of aluminum oxide and 5 mL of ammonia water to 100 mL of ethanol and mix well. Then add 1.5 mL of 3-aminopropyltrimethoxysilane. Stir in a sealed container at 45° C. and 300-500 rpm for 10 h to perform modification.
[0112] (2) Same as Example 1, specifically: after the reaction is complete, the modified particles are washed with ethanol and centrifuged at 8000 r / min for 10 minutes 3 times to obtain 30-40% solid content precipitated modified particles. Ethanol is added again and dispersed at 300W ultrasonic for 10 minutes to obtain 10wt% modified nanoparticles.
[0113] (3) The same as Example 1, specifically: take 50g of sample and add 10g of epoxy resin diluted to 10wt% by ethanol and 1g of amine curing agent, use an emulsifier at 12000r / min for shear emulsification and dispersion for 10 minutes to obtain a super amphiphobic coating.
[0114] (4) Same as Example 1, specifically: the substrate is cleaned alternately with ethanol and water, and the coating is evenly sprayed on the surface of the substrate with a spray gun (nozzle diameter: 1 mm) at a pressure of 0.5 MPa, with a quantitative of 1 g / ㎡. First, it is cured at a low temperature of 60°C for 3 hours, and then at a high temperature of 120°C for 3 hours.
[0115] Comparative Example 5
[0116] Different from Example 3, the long-chain perfluorosilane in step (1) is replaced by a short-chain perfluorosilane.
[0117] Comparative Example 6
[0118] The difference from Example 3 is that the 3-aminopropyltrimethoxysilane in step (1) is replaced by trimethoxysilane that does not contain ammonia.
[0119] Comparative Example 7
[0120] The difference from Example 3 is that the order of adding the long-chain perfluorosilane and 3-aminopropyltrimethoxysilane in step (1) is adjusted to: first add 3-aminopropyltrimethoxysilane and then add the long-chain perfluorosilane.
[0121] Comparative Example 8
[0122] The difference from Example 3 is that in step (3), mixing is performed directly without high shear emulsification.
[0123] Performance Testing
[0124] The relevant properties of the new model of durable super-hydrophobic microstructure coating prepared by Examples 1 to 5 and Comparative Examples 1 to 8 of the present invention were tested.
[0125] Water, glycerol and ethylene glycol contact angle (CA) test: GB / T 30447-2013 nano film contact angle measurement method is used; wear resistance hydrophobic and oleophobic test: use a 200g weight to wear 30 times and then measure the contact angle; weather resistance test: soak the super-amphiphobic sample in ethylene glycol for 24 hours and then measure the contact angle. Among them, the substrate used in the test is a glass plate, and the test time is 10s.
[0126] Table 1 Performance of anti-wear and weather-resistant super-amphiphobic material coating examples and comparative examples
[0127]
[0128]
[0129] As can be seen from Examples 1-5, the wear-resistant and weather-resistant super-amphiphobic material coating of the present invention can achieve the amphiphilic function of water and glycerol by adjusting the proportion of each component, and has certain wear resistance and weather resistance. As can be seen from Examples 1, 3 and Comparative Example 4, perfluorodecyl triethoxysilane provides a sufficiently low surface energy, which is the key to achieving super-amphiphobicity, but too much perfluorodecyl triethoxysilane will affect the secondary grafting of 3-aminopropyl trimethoxysilane. As can be seen from Examples 3, 4 and Comparative Example 4, the introduction of 3-aminopropyl trimethoxysilane provides a robust connection force for super-amphiphobic nanoparticles under the use of a small amount of epoxy resin; as can be seen from Examples 2, 4, 5 and Comparative Examples 1, 2, 3, too much resin will cover the nanoparticles. With the continuous grafting reaction of long and short chains, the surface hydroxyl groups of the nanoparticles are fully reacted, and even in the long-term immersion of ethylene glycol, good stability is maintained, overcoming the functional failure of local defects of nanoparticles in harsh environments. From the comparison between comparative examples 5, 6, 7, and 8 and the embodiment, it can be seen that the long-chain fluorocarbon silane provides a lower surface energy; 3-aminopropyltrimethoxysilane provides a more robust connection between the nanoparticles and the resin, and has a better anti-wear performance; however, if 3-aminopropyltrimethoxysilane is added first to react preferentially, the long-chain fluorosilane does not have enough grafting sites, and the amphiphilic functionalization cannot be achieved; shear emulsification allows the amino groups grafted on the surface of the nanoparticles to fully contact with the resin, reducing the agglomeration of the nanoparticles, thereby forming a continuous and stable coating structure
[0130] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A wear-resistant and weather-resistant super-amphiphobic coating, characterized in that: The wear-resistant and weather-resistant super-amphiphobic coating comprises modified nanoparticles, epoxy resin and curing agent, wherein the modified nanoparticles are obtained by fluorination-modifying the nanoparticles with long-chain perfluorosilane and then grafting them with aminosiloxane; wherein, The mass ratio of epoxy resin, curing agent and modified nanoparticles is (1-2):(1-2):5; The mass ratio of long-chain perfluorosilane, nanoparticles and aminosiloxane is (1-3):1:(0.5-1).
2. The wear-resistant and weather-resistant super-amphiphobic coating according to claim 1, characterized in that: The mass ratio of epoxy resin, curing agent and modified nanoparticles is (1-1.5):(1-1.5):5; The mass ratio of long-chain perfluorosilane, nanoparticles and aminosiloxane is (2-3):1:(0.75-1).
3. The wear-resistant and weather-resistant super-amphiphobic coating according to claim 1 or 2, characterized in that: The nanoparticles are selected from one or more of aluminum oxide, aluminum hydroxide, silicon dioxide and diatomaceous earth, preferably aluminum oxide; Preferably, the particle size of the nanoparticles is 5-30 nm; Preferably, the long-chain perfluorosilane is selected from one or more of 1H,1H,2H,2H-perfluorodecyltriethoxysilane, tridecafluorooctyltrimethoxysilane, 1H,1H,2H,2H-perfluorododecyltriethoxysilane, heptadecafluorodecyltrimethoxysilane and 1H,1H,2H,2H-perfluorododecyltrichlorosilane; Preferably, the aminosiloxane is selected from one or more of 3-aminopropyltrimethoxysilane, 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane, N-[3-(trimethoxysilyl)propyl]ethylenediamine and 1-(3-trimethoxysilyl)propylurea; Preferably, the epoxy resin is a bisphenol epoxy resin, and the bisphenol epoxy resin is a bisphenol A epoxy resin; Preferably, the curing agent is an amine curing agent, and the amine curing agent is selected from one or more of ethylenediamine, diethylenetriamine and triethylenetetramine.
4. A method for preparing the wear-resistant and weather-resistant super-amphiphobic coating according to any one of claims 1 to 3, characterized in that: The following steps are involved: The nanoparticles are added to an alkaline alcohol solution for activation, and then long-chain perfluorosilane is added for fluorination modification, and then aminosiloxane is added for grafting reaction to obtain modified nanoparticles; The modified particles are mixed and emulsified with an alcohol-diluted epoxy resin and a curing agent to obtain a super-amphiphobic coating.
5. The preparation method according to claim 4, characterized in that: In the alkaline alcohol solution, the base is aqueous ammonia; the alcohol is ethanol; preferably, the volume ratio of the base to the alcohol is (1-3):50; Preferably, the fluorination modification is carried out by stirring the reaction at 40-50°C and 300-500 rpm for 3-6 hours; Preferably, the grafting reaction is carried out at 40-50°C with a sealed stirring speed of 300-500 rpm for 8-12 hours; Preferably, after the grafting reaction, the reactants are washed with alcohol and centrifuged to obtain sinking modified particles with a solid content of 30-40%, and alcohol is added to the sinking modified particles for physical dispersion to obtain 10-15wt% modified nanoparticles; Preferably, the centrifugation condition is 5000-9000 r / min for 5-20 minutes; Preferably, the physical dispersion is performed by ultrasonic dispersion, the ultrasonic frequency is 200-400W, and the ultrasonic time is 5-20min; Preferably, in the alcohol-diluted epoxy resin and curing agent, the mass fraction of the epoxy resin is 10-15wt%; Preferably, the mixing and emulsification is emulsification and dispersion under high shear of 10000-15000 r / min for 5-20 minutes.
6. A method for preparing an anti-wear and weather-resistant super-amphiphobic coating using the anti-wear and weather-resistant super-amphiphobic coating according to any one of claims 1 to 3, characterized in that: The following steps are involved: The substrate is surface treated, and then the wear-resistant and weather-resistant super-amphiphobic coating according to any one of claims 1 to 3 is sprayed on the surface of the substrate, first cured at a low temperature of 50-80° C. for 1-5 hours, and then cured at a high temperature of 100-130° C. for 1-5 hours.
7. The preparation method according to claim 6, characterized in that: The surface treatment of the substrate comprises cleaning the substrate alternately with ethanol and water; Preferably, the spraying is carried out at an air pressure of 0.2-6 MPa; Preferably, when sprayed on the surface of the substrate, the quantitative amount is 0.7-1.2g / m 2 .
8. A wear-resistant and weather-resistant super-amphiphobic coating obtained by the preparation method according to claim 6 or 7.
9. The wear-resistant and weather-resistant super-amphiphobic coating according to claim 8, characterized in that: The static contact angle of the wear-resistant and weather-resistant super amphiphobic coating to water is 153°-165°, and the static contact angle to glycerol is 151°-160°; after 30 times of wear, the static contact angle to water is 160°-161°, and the static contact angle to glycerol is 150°-152°; after immersion in ethylene glycol for 24 hours, the static contact angle of the wear-resistant and weather-resistant super amphiphobic coating is 154°-155°.
10. Use of the wear-resistant and weather-resistant super-amphiphobic coating according to any one of claims 1 to 3 or the wear-resistant and weather-resistant super-amphiphobic coating according to claim 8 or 9 in the fields of construction, transportation or marine engineering.
Citation Information
Cited By
A coating material with long-acting super-amphiphobic property, a coating layer and a preparation method thereof
CN122628633A